Attitudes toward romantic love and the spouse selection criteria of UPV-CAS senior students. - Panaligan, Anna Liza C
This was a study on the attitude toward romantic love and the spouse selection patterns of UPV college students. It was the aim of the study to determine UPV students' attitudess toward romantic love, to find out the characteristics these students look for in the potential marriage partners and to know if there was difference between males' and females' attitudes toward romantic love and in the selection of their future mates. The hypotheses of the study were: 1) there was a difference between the attitude of males and females toward romantic love; and 2) there was a difference in the mate selection criteria of males and females. The knox-Sporakawski Attitudes Towards Romantic Love Scale consisting of 29 statements about the nature of love was used to measure romantic love. Another questionnaire was employed to determine the attributes that a prospective marriage partner might possess. These were administered to randomly selected senior students of the UPV-CAS. Results showed that there were no significant differences in both the attitudes of male and female students toward love and their spouse selection criteria.